Latyfundia książąt Zbaraskich w XVI i XVII wieku - Anusik, Zbigniew (Przegląd Nauk Historycznych, 2009)
The article is about the process of establishing the latifundia of one of the richest magnates' family in the history of Polish Noble Republic in the 16th and 17th century. The princes' Zbaraski traced their origin back to Fedor prince Nieświski. Their patrimony was the southern part of province of Wołyń. Here in the Krzemieniec County they had their families' estates. Four sons of Andrzej prince Zbaraski and Hanna Herburt originated four branches of the family. The second son of the mentioned couple, Stefan prince Zbaraski (d. 1585), voivod of Troki, thanks to three profitable marriages and his own cunningness established the great latifundia which were composed of 7 towns and about 175 villages at Wołyń and Lithuania. However. he did not have sons and all estates of voivod of Troki inherited his unique daughter. Barbara, who married count Gabriel Tęczyński in 1602. The third son of Andrzej prince Zbaraski, prince Jerzy (d. 1580), was the owner of landed estates at Wołyń and Lithuania. He was married twice. His latifundia consisted of 50-60 villages. After his death his estates were inherited by his two living brothers and nephew (Wołyń estates) and two daughters from the first marriage (Lithuanian estates). The youngest son of Andrzej prince Zbaraski, prince Władysław (d. 1581/1582). was also the poorest of all brothers. His estates consisted of about 30 villages at Wołyń and a few villages at Kijów voivodship. His landed estates were inherited by three of his sons, prince Piotr (d. 1604), prince Konstanty (d. 1592) and prince Stefan (d. 1605). Only the eldest of them, Piotr prince Zbaraski, enlarged his estates thanks to the profitable marriage with Ewa princess Wiśniowiecki. Because of their fortunes all sons of prince Władysław belonged to the rich nobility rather than to the magnates. All of them died childless. The greatest career regarding politics and fortune fell to the descendents of the eldest son of Andrzej prince Zbaraski and Hanna Herburt, prince Mikołaj (d. 1574), starost of Krzemieniec. His only son, Janusz (d. 1608), voivod of Bracław, married the rich heiress of landed estates in Bracław voivodship, Anna princess Czetwertyński. He was a very good husbandman who providently enlarged his fortune. During three decades he built the great latifundia in three voivodships: Wołyń, Bracław and Kijów. The huge fortune of Janusz prince Zbaraski consisted before his death of about 200 towns and villages. 1Wosons of prince Janusz, prince Jerzy (d. 1631) and prince Krzysztof (d. 1627), belonged to the exclusive group of the richest Crown magnates. Both of them played a great political role during the reign of Zygmunt III Waza. Mer death of the younger brother, the only heir of the huge family landed estates was Jerzy prince Zbaraski, castellan of Kraków. During the years 1613-1631 he bought a few landed estates in Kraków voivodship (2 towns and about 40 villages). When he died, he left the latifundia which consisted of 49 towns and about 330 villages. Because of his fortune the castellan of Kraków was the second Crown magnate of his times (richer was only Władysław Dominik prince Zasławski). Jerzy prince Zbaraski died childless as the last male descendent of famous princes' Zbaraski family. Mter his death the huge latifundia of Zbaraski family were divided between the families of princes' Wiśniowiecki and Warszycki. A little part of the castellan of Kraków legacy was also obtained by the family of princes' Czetwertyński.